2021
DOI: 10.3389/fmicb.2021.659315
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics of Environmental Microbial Communities. II: Characterization Using Molecular Networking and Information Theory

Abstract: Structurally diverse, specialized lipids are crucial components of microbial membranes and other organelles and play essential roles in ecological functioning. The detection of such lipids in the environment can reveal not only the occurrence of specific microbes but also the physicochemical conditions to which they are adapted to. Traditionally, liquid chromatography coupled with mass spectrometry allowed for the detection of lipids based on chromatographic separation and individual peak identification, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 95 publications
0
31
0
Order By: Relevance
“…We compare these findings with previous studies, which have examined the lipidome of the Black Sea water column using traditional IPL identification (e.g., Neretin et al, 2007;Wakeham et al, 2007;Schubotz et al, 2009;Sollai et al, 2018). Our rapid visualization method lays a foundation for the study of Ding et al (2021), reported in parallel to this study, which used information theory framework combined with molecular networking to investigate lipid diversity and specificity as well as identify novel lipids.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We compare these findings with previous studies, which have examined the lipidome of the Black Sea water column using traditional IPL identification (e.g., Neretin et al, 2007;Wakeham et al, 2007;Schubotz et al, 2009;Sollai et al, 2018). Our rapid visualization method lays a foundation for the study of Ding et al (2021), reported in parallel to this study, which used information theory framework combined with molecular networking to investigate lipid diversity and specificity as well as identify novel lipids.…”
Section: Introductionmentioning
confidence: 59%
“…At its maxima at 130 mbsl, at the top of the euxinic zone, it is most probably associated with SRB. Three components were 1deoxyceramides and two were sulfono-1-deoxyceramides (as per their assignment in Ding et al, 2021). Also present were two PGs, one with a DAG 33:1 core and one with a 32:0 core.…”
Section: Rapid Clustering Of Lipids Based On Depth Profile Similaritymentioning
confidence: 86%
See 3 more Smart Citations